Professional mental health aid for children, adolescents, and young adults during COVID-19 in Flanders, Belgium - Muysewinkel, Emilie; Vesentini, Lara; Van Deynse, Helena; Vanclooster, Stephanie; Kinderrechten, Kenniscentrum; Devarwaere, Sofie; Bilsen, Johan; Van Overmeire, Roel (Frontiers in Public Health, 2025)
Few studies have investigated whether children, adolescents, and young adults (aged 10–25 years) had access to professional mental health aid when they desired it during the coronavirus disease 2019 (COVID-19) pandemic. An online survey was conducted in Flanders, Belgium, to examine professional mental health aid access (PMHAA). In total, 982 respondents were included, of whom the majority were between 13 and 15 years old (44.8%) and female (81.4%). Of these, 64.8% felt a need for PMHAA. Of those wanting PMHAA, only 29.6% had an appointment with a mental health professional. Those who did not have PMHAA mostly did not do so because of fear of stigma (54%), not knowing where to search for professional mental health aid (38.2%), and finding the aid to be too expensive (12.9%). This study’s findings indicate a large unmet need for professional mental health aid during the COVID-19 pandemic among people aged between 10 and 25 years old. There is a need for a campaign to reduce mental health stigma in this population.